Cell:cell adhesion in sweet cherry fruit primarily due to pectins - Culemann, Elsa; Schumann, Christine; Winkler, Andreas; Sitzenstock, Simon; Knoche, Moritz (Frontiers in Plant Science, 2026)
Rain cracking limits the production of sweet cherries wherever they are grown. Cracking occurs by the separation of neighboring cells along their cell walls (by cell:cell separation). The objectives were to identify the cell wall components involved in cell:cell adhesion using immunolabeling and monoclonal antibodies (mAbs) and digestion assays employing pectinases, hemicellulases, and a cellulase. The mAbs identified homogalacturonans (LM19 and LM20), arabinans (LM6), and (to a lesser extent) xyloglucans (LM25) in skin, parenchyma, xylem, and phloem. Galactan (LM5) occurred only in the phloem, and xylan/arabinoxylan (LM11) occurred only in the xylem. Digestion of parenchyma by polygalacturonase (PGase) increased with time and concentration. Throughout development, digestion was highest by galactanase (GALase), followed by PGase and pectate lyase (PLase). Digestion by the hemicellulases xylanase (XYLase), xyloglucanase (XGase), and mannanase (MANase) was lower. The lowest digestion was due to cellulase (CELase). Incubation in pectinases released more cells, protoplasts, and cell wall fragments than incubation in hemicellulases or CELase. Storage duration had no effect on the digestion of cell walls. Digestion of parenchyma by native enzymes from fruit juice was similar to that by purified enzymes. Boiling juice to destroy enzyme decreased digestion. Adding Ca reduced digestion by PGase. Extracting and complexing Ca by EGTA increased digestion. Across eight cultivars, GALase, PGase, and PLase digested more cell walls than hemicellulases or cellulase. Within pectinases, GALase, PGase, and PLase were equally effective in “Adriana”, whereas in “Kordia”, PGase was more effective than GALase and PLase. In “Flamengo Srim”, “Regina”, and “Staccato”, digestion by GALase, PGase, and PLase was low. We conclude that pectins are primarily responsible for cell:cell adhesion in sweet cherry fruit. Further studies should therefore explore the relationship between cell wall chemistry, Ca status, and cell:cell adhesion.